Differences and Correlations of Morphological Characteristics and Fatty Acid Profiles of Seeds of Toona sinensis. Issue 11 (27th October 2020) - Su, Shang; Wang, Li‐Jin; Ni, Jian‐Wei; Geng, Yong‐Hang; Xu, Xin‐Qiao
Abstract: Toona sinensis (A.Juss.) M.Roem., a multi‐purpose tree of Meliaceae, is widely distributed and intensively cultivated in Asia, yet its high yielding, lipid‐rich seeds are rarely exploited. The present study systematically analyzed the differences and correlations of seed morphological characteristics and fatty acid (FA) profiles of 62 representative T. sinensis germplasms distributed across northern to southern China. T. sinensis seeds were rich in total FAs (TFA, 107.03–176.18 mg/g). Additionally, linoleic acid (54.69–100.59 mg/g), α ‐linolenic acid (ALA, 22.47–45.02 mg/g), oleic acid (OA, 5.12–23.94 mg/g), palmitic acid (6.87–14.14 mg/g), stearic acid (SA, 3.13–6.57 mg/g) and elaidic acid (1.70–2.88 mg/g) were the major FAs measured by GC/MS analysis. Size (average width of 3.94±0.01 mm and length of 5.79±0.02 mm) and mass (average thousand‐seed weight of 10.52±0.17 g) were greater in T. sinensis seeds collected south than north of 30° latitude. These traits were also positively correlated with unsaturated FA content and negatively related to SA and saturated FA contents ( P <0.05). Significant positive correlations were found between seed length and polyunsaturated FA (R 2 =0.370) and ALA levels (R 2 =0.296), as well as between thousand‐seed weight and monounsaturated FAs (R 2 =0.309) and OA levels (R 2 =0.297) ( P <0.05). Seventeen T. sinensis germplasms gathered by cluster analysis as cluster IV were determined as desirable for oil processing due to their higher TFA and ALA contents and greater seed size and mass than others. Generally, the wider, heavier, and especially longer seeds of T. sinensis contain much higher levels of FAs, especially ALA, and are the more promising sources for breeding and the oil processing industry. Abstract :